Classification of videogames for amblyopia treatment in perceptive and cognitive domains - Laura Asensio-Jurado; Marc Argilés; Paula Gil-Llansa; Lluïsa Quevedo-Junyent (PLoS ONE, 2025)
Video games are increasingly used in vision science and clinical interventions, particularly in the treatment of amblyopia. Among them, action video games have shown promise in enhancing visual functions such as attention, spatial resolution, and contrast sensitivity. However, the classification of games in current studies typically relies on broad commercial genre labels, which lack functional specificity and fail to capture the perceptual, cognitive, and motor demands relevant to therapeutic use. This imprecision can lead to suboptimal game selection and limit comparability across studies. To address this gap, we developed a data-driven framework to classify commercial video games based on functional load profiles. Twelve experts evaluated seven games across nine dimensions derived from prior literature on action video games, including Perceptual Load , motor demands, Working Memory , and attentional control. We applied Multidimensional Scaling and K-means clustering to group games based on similarity ratings, and validated the structure using Principal Component Analysis. Three distinct clusters emerged: (1) Action video games with high motor and Perceptual Load (e.g., Call of Duty , Unreal Tournament ); (2) puzzle and arcade games with moderate visuomotor and cognitive engagement (e.g., Tetris , Pac-Man ); and (3) low-demand simulation games ( The Sims ). Notably, Tetris reflected moderate visuomotor but higher cognitive demands, confirming its hybrid profile. This multidimensional classification provides a reliable and objective tool to guide therapeutic video game selection and development, offering a valuable alternative to the subjective genre-based selection of video games in both research and clinical applications.